The effects of social support and having a partner on sleep quality in dementia - Eshkoor, Sima Ataollahi; Tengku Abdul Hamid, Tengku Aizan; Hassan Nudin, Siti Sa'adiah; Chan, Yoke Mun (Sage Publications, 2013)
Objectives: This study aimed to determine the effects of social support and having a partner on sleep quality in the elderly patients with dementia. Methodology: This research was conducted on 1210 noninstitutionalized elderly Malaysian individuals with dementia. The effects of age, ethnicity, educational level, marital status, sex differences, social support, and having a partner on sleep quality were evaluated in the respondents. The multiple logistic regression analysis was used to predict the risk of sleep disturbances among the participants. Results: Approximately, 41% of the participants experienced sleep disruption. Further findings showed that ethnicity (odds ratio [OR] = 0.62), social support (OR = 1.35), marital status (OR = 2.21), educational level (OR = 0.65), and having a partner (OR = 0.45) significantly affected sleep quality (P < .05). Sex differences and age were unrelated predictors of sleep disturbances (P > .05). Conclusion: It was concluded that social isolation and being single increased sleep disruption among respondents, but having a partner and ethnic non-Malay decreased the rate of sleep problems.